“Sistema educacional inclusivo”: um olhar para a formação de conceitos em estudantes com deficiência intelectual - Ferraz, Ana Paula dos Santos (2017)
This master study is affiliated to the Postgraduate Program in Education, to the Research Line in Special Education and to the Study and Research Group in Education Psychology and Inclusive Education – GEPEIN – at Federal University of Santa Maria. The study was based on the National Policy on Special Education from the Inclusive Perspective (BRASIL, 2008), since this is the policy that guides the teaching systems. This investigation aims to understand how a national policy that intents the education inclusion can or cannot contribute to students with intellectual disabilities in terms of learning, formation of concepts and knowledge consolidation. It was carried out through a case study, because it is a study that allows a deep understanding of the facts and phenomena, and a student identified with intellectual disability included in the regular classroom in the third year of high school State public institution of the city of Nova Palma / RS. Through a qualitative approach, a documentary research with the student’s descriptive reports and interviews with Portuguese, Mathematics and Special Education teachers was carried out. The analysis on these data followed Bardin’s technique on content analysis (2011). The theoretical background was mostly based on Vygotskian Cultural-Historical Theory to concept formation. This theory presents the scientific concepts as those systematically appropriated through teaching that require the spontaneous concepts appropriated from the child’s practice and experience with their surroundings. The initial findings showed difficulties in relation to the documents, such as lack of patterns to report the results on the student’s evaluations. The results also presented difficulties to identify and constitute the Special Education target audience. The data on the scientific concepts analysis revealed that the student showed progresses, but she also had difficulties in more abstract issues. Therefore, the National Policy on Special Education from the Inclusive Perspective (BRASIL, 2008) ensured the student’s access to a regular school, as well as, improvements to institutions, since it organized the system to receive these students. However, few changes were achieved in formal learning.